Peran Ibu Dalam Menumbuhkan Minat Literasi Pada Anak Prasekolah - Sari, Amallia Putri Kartika; Ruhaena, S.Psi, M.Si, Psi, Dr. Lisnawati Ruhaena, S.Psi, M.Si, Psi (2017)
This research aimed at understanding the roles of the mothers in inculcating preschool childrens interests in literacy. Informants in this study had criteria: (a) mothers have preschool children of Surakarta (housewife and working mothers) (b) the children studying at Aisyiyah 14 Danukusuman kindergarten (c) live with her children. This research is using qualitative phenomenological approach, which the data collected through interview, observation and documentation. The results of this study showed that overall the mother has a willingness to foster interest in literacy. Mothers who work as a role assisting working mothers and children waited to learn and to help the electoral process of learning media. As for the mother who works as a housewife rather to teach and repeat the course material at home, read books and study material balance between home and school. Awareness to foster interest in literacy in preschool children is better done by housewives. Involvement done by housewives rather to direct, guide, and provide time for children. Activity literacy reading and writing is done at home by a certain time span to provide an understanding early on to start growing interest in child literacy. Factors supporting the mother's role in growing interest in child literacy readiness factors include the age of the child to receive a stimulus, the child's ability, the method used, the media used as well as supporting facilities literacy activities. Factors inhibiting the mother's role in growing interest in child literacy that is derived from the constraints of the mother and child constraints. Constraints experienced by the mother, such as: irritability, lack of patience and had to remind the child related the alphabet, while the child constraints, such as: the child easy to feel tired and bored and less focused.